PENGEMBANGAN MEDIA FLIPBOOK DIGITAL BERBASIS AUGMENTED REALITY PADA MATERI KERAGAMAN BUDAYA INDONESIAKU KELAS V SEKOLAH DASAR - Dewa Gede Divayanha; Ni Putu Candra Prastya Dewi; Ni Nyoman Kurnia Wati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of technology has a significant impact on the world of education that can be used as an intermediary to achieve learning objectives and improve the learning process to be more interactive, this study was conducted with the aim of producing an interactive learning media in the form of a Digital Flipbook media based on Augmented Reality (AR) on the material "My Indonesian Cultural Diversity" for Grade V at SDN 2 Alasangker which is valid and practical. This research method uses Research and Development with the ADDIE development model including Analysis, Design, Development, Implementation, and Evaluation. The ADDIE model used is limited to the implementation stage due to time constraints. Data collection techniques used include interviews, documentation, and questionnaires. The results of the study show that the Digital Flipbook learning media based on Augmented Reality obtained a "very high" validity value, namely 0.92 for media experts, 0.92 for language experts, and 0.91 for material experts. In the practicality test using a questionnaire with respondents of 2 fifth-grade teachers and 39 fifth-grade students. The results of the practicality obtained a score of 97% for the practicality test of practitioners (teachers) and 94% for the practicality test of students. Based on these data, the research on the development of Augmented Reality-based Digital Flipbook learning media on the material "My Indonesian Cultural Diversity" for fifth-grade students is categorized as very feasible and practical to use.